(3LSQ GdEJUGd hGdfLGM s - (3SejQ(B, (3eWGhYs ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2019)
(3JfGhd gPG GdcJGH ehVhY GdYdGbGJ GdYGeI ef MjK Gdeaghe hGdOhQ aj YGde GdCYeGd, ceG Cfg JWQb Gdi GdYdGbGJ GdYGeI hhSGFd GdEJUGd GdLeGgjQj, HGdEVGaI Gdi JfXje HQGeL hMedGJ GdYdGbGJ GdYGeI hGdaYGdjGJ GdJj JhdO GdGgJeGe, hCNjQG bGe HYQV YOI MGdGJ OQGSI aj GdehVhY(B.s
(3GdedGMb U(B.336 s
Keywords: (3GdYdGbGJ GdYGeIs; (3GdYdGbGJ GdYGeIs; (3GdYdGbGJ GdYGeI(B: (3COhGJ GdGJUGd GdLeGgjQjs